Link Aggregation Control Protocol on Software Defined Network - L. D. Irawati; Y. Sun Hariyani; S. Hadiyoso (International Journal of Electrical and Computer Engineering (IJECE), 2017)
A physical connection of computer network must be made reliably. Breaking connection will cause communication between nodes (for example routers, switches, hosts) can be disconnected. One of the solutions is implemention of link aggregation (LA). LA integrates several of physical ports together to make a single logical communication link. Accordingly, there is load sharing traffic among the member port of the group, high-throughput increasing via a single link, and redundancy providing for broken links. We present the implementation of link aggregation using Ryu controller on Software Defined Network (SDN) topology. The results show that the implementation of SDN with OpenvSwitch and Ryu controller can successfully run link aggregation function to solve the problem of link failure.